CONSENT FOR SURGERY - WHEN SHOULD IT BE TAKEN - De zoysa, M.I.M.; De Silva, S.K.L.A. (My University, 2012)
The quality and the quantity of the information required in the consent process prior to surgery are well documented. The time at which the consent should be taken is another important issue that had not been evaluated properly.